2009
DOI: 10.1098/rspb.2009.1592
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reorganization of the transcriptional regulatory network after genome duplication in yeast

Abstract: I study the reorganization of the yeast transcriptional regulatory network after whole-genome duplication (WGD). Individual transcription factors (TFs) were computationally removed from the regulatory network, and the resulting networks were analysed. TF gene pairs that survive in duplicate from WGD show detectable redundancy as a result of that duplication. However, in most other respects, these duplicated TFs are indistinguishable from other TFs in the genome, suggesting that the duplicate TFs produced by WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…It is now well accepted that this mechanism has contributed to the evolution of genomes and their regulatory networks. Several studies [56][57][58][59] have investigated the role of WGD on network evolution. Such studies have revealed that (i) genes targeted by many TFs appear to be preferentially retained in duplicate after WGD, (ii) duplicate TFs produced by WGD rapidly evolve to perform distinct functional roles in the regulatory network, (iii) newly formed transcriptional pathways remain connected (paths are not broken) and are preferentially cross-connected with ancestral ones, and (iv) duplicated TFs through WGD may have contributed to the evolution of some network motifs in yeast.…”
Section: Impact Of Gene Duplication On Trn Evolutionmentioning
confidence: 99%
“…It is now well accepted that this mechanism has contributed to the evolution of genomes and their regulatory networks. Several studies [56][57][58][59] have investigated the role of WGD on network evolution. Such studies have revealed that (i) genes targeted by many TFs appear to be preferentially retained in duplicate after WGD, (ii) duplicate TFs produced by WGD rapidly evolve to perform distinct functional roles in the regulatory network, (iii) newly formed transcriptional pathways remain connected (paths are not broken) and are preferentially cross-connected with ancestral ones, and (iv) duplicated TFs through WGD may have contributed to the evolution of some network motifs in yeast.…”
Section: Impact Of Gene Duplication On Trn Evolutionmentioning
confidence: 99%
“…Given that previous work in allopolyploids (e.g. wheat (Pfeifer et al ., ) and cotton (Hu et al ., )) was mainly based on aggregated co‐expression relationships of homoeologs, one future direction is to generate networks considering homoeolog expression separately, thereby allowing the direct evaluation of topological dynamics in terms of gain and loss of intra‐ and inter‐subgenome relationships (Conant & Wolfe, , ; Conant, ). Although co‐expression relationships do not necessarily represent physical interactions between cis and trans regulatory elements, the gene‐to‐gene interconnections that are inferred based on the ‘guilt‐by‐association’ principle provide an alternative and parallel approach for understanding the impact of genomic merger and doubling, under the same analytical framework used for genes outside of a network context.…”
Section: The Extended Cis–trans Framework and Expression Patterns In mentioning
confidence: 99%
“…Whole genome duplications and small-scale duplications have very different consequences. Selective retention of different duplicates, and enrichment of signaling proteins and transcription factors, have been observed in yeast, plants, early vertebrate and fish following whole genome duplications (Conant 2010;Gout, Duret and Kahn 2009;Huminiecki and Heldin 2010;Kassahn et al 2009;Manning and Scheeff 2010). This indicates that the individual duplication of signaling proteins and transcriptional regulators may be deleterious, since interactions between them are relatively transient and subtle, requiring a dosage balance from the whole genome duplication to survive.…”
Section: Regional Duplicationmentioning
confidence: 99%